Arsenic removal from highly-acidic wastewater with high arsenic content by copper-chloride synergistic reduction. (January 2020) - Wang, An; Zhou, Kanggen; Zhang, Xuekai; Zhou, Dingcan; Peng, Changhong; Chen, Wei
Abstract: A synergistic combination of chloride and copper powder was proposed as a new method to reductively remove arsenic from highly-acidic wastewater with high arsenic content (HAWA). As(III) was reduced to As(0) by copper powder in the presence of chloride and were effectively removed from HAWA. The procedure to remove arsenic was optimized as follows: initial H + concentration of 5 mol L −1, Cu-to-As molar ratio of 8, Cl-to-As molar ratio of 10, a reaction temperature of 60 °C, copper powder particle size of 68–24 μm, and a stirring speed of 300 r min −1 . Under these optimal conditions, the removal rate of arsenic was close to 100%. Kinetics results suggested that the arsenic removal process was controlled by both diffusion and chemical reactions with an apparent activation energy of 29.78 kJ mol −1 . The XRD results showed that the removed arsenic in the residue existed primarily in the form of AsCu3 alloy. Graphical abstract: Image 104272 Highlights: Reductive removal of arsenic was achieved via chloride-copper synergy. Arsenic was almost completely removed from the highly-acidic wastewater. Arsenic removal process was controlled by both diffusion and chemical reaction. Arsenic in the residue was in the form of AsCu3 alloy.